The Impossible First: From Fire to Ice-Crossing Antarctica Alone - Colin O'Brady (USA Scribner, 2020)
Prior to December 2018, no individual had ever crossed the landmass of Antarctica alone, without support and completely human powered. Yet, Colin O'Brady was determined to do just that, even if, ten years earlier, there was doubt that he'd ever walk again normally. From the depths of a tragic accident, he fought his way back. In a quest to unlock his potential and discover what was possible, he went on to set three mountaineering world records before turning to this historic Antarctic challenge. O'Brady's pursuit of a goal that had eluded many others was made even more intense by a head-to-head battle that emerged with British polar explorer Captain Louis Rudd-also striving to be "the first." Enduring Antarctica's sub-zero temperatures and pulling a sled that initially weighed 375 pounds-in complete isolation and through a succession of whiteouts, storms, and a series of near disasters-O'Brady persevered. Alone with his thoughts for nearly two months in the vastness of the frozen continent-gripped by fear and doubt-he reflected on his past, seeking courage and inspiration in the relationships and experiences that had shaped his life.
Keywords: Nonfiction; Adventure; Memoir; Biography; Travel; Sports; Nature